FACTORS INFLUENCING E-COMMERCE ADOPTION BY SMES INDONESIA: A CONCEPTUAL MODEL - Triandini, Evi; Djunaidy, Arif; Siahaan, Daniel (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi, 2015)
E-commerce present different prospect to Small and Medium Sized Enterprises (SMEs) andprovides benefits to SMEs. At this stage, there are a number of studies focused on SMEs indeveloped countries. For developing countries, the situation is quite different. Furthermore, thereis still limited number of researches on e-commerce adoption by SMEs in Indonesia. SMEs playa vital role in reducing the rate of poverty and unemployment in Indonesian economy. In 2009,micro, small and medium enterprises in Indonesia consist of 52.7 million units or 99.99% of thetotal business enterprises, and employ 96.21 million people or 97% of the total labor forces. SMEsin Indonesia faced internal and external problems. This study explores various factors influencinge-commerce adoption by SMEs in several countries and projecting it to Indonesia. Results showsthat there are a number of perceived opportunities presented by e-commerce adoption inIndonesia, i.e. extending market-reach and even global, increasing customer personalizeservices, and improving its competitiveness. Furthermore, this study also proposes six potentialfactors influenced the adoption of e-commerce by SMEs in Indonesia, i.e. perceived usefulness,perceived ease of use, relative advantage, perceived risk, perceived trust, and compatibility.
Keywords: e-commerce; adoption factors; small and medium-sized enterprises (SMEs)